Biallelic variants in BRCA1 gene cause a recognisable phenotype within chromosomal instability syndromes reframed as BRCA1 deficiency. Issue 9 (25th August 2020) - Chirita-Emandi, Adela; Andreescu, Nicoleta; Popa, Cristina; Mihailescu, Alexandra; Riza, Anca-Lelia; Plesea, Razvan; Ioana, Mihai; Arghirescu, Smaranda; Puiu, Maria
Abstract : Pathogenic variants in BRCA1 gene in heterozygous state are known to be associated with breast-ovarian cancer susceptibility; however, biallelic variants cause a phenotype recognised as Fanconi anaemia complementation group S. Due to its rarity, medical management and preventive screening measures are insufficiently understood. Here, we present nine individuals (one new and eight previously presented) with biallelic variants in BRCA1 gene, to delineate clinical features in comparison with other chromosome instability syndromes and understand the patients' health risk. Features seen in these 9 individuals (7 females/2 males) include prenatal and postnatal growth failure (9/9), microcephaly (9/9), hypo/hyperpigmented lesions (9/9), facial dysmorphism (9/9), mild developmental delay (8/9) and early-onset solid tumours (5/9). None presented bone marrow failure or immunodeficiency. Individuals with biallelic variants in BRCA1 also showed chromosomal instability by mitomycin and diepoxybutane test. The phenotype caused by biallelic BRCA1 variants is best framed between Fanconi anaemia and Nijmegen syndrome, yet distinct due to lack of bone marrow failure and immunodeficiency. We hypothesise that disease class should be reframed and medical management in people with biallelic variants in BRCA1 should emphasise on detection of solid tumour development and avoiding exposure to ionising radiation.